Morphometric measurements of sheep fed with increasing levels of sunflower meal - Silva, Neyton Carlos da; Gaspar, Raphael Colombo; Chaves, Amália Saturnino; Geraseev, Luciana Castro; Athayde, André Luiz Mendes; Crocomo, Letícia Ferrari (Acta Scientiarum. Animal Sciences, 2019)
The objective of this work was to evaluate the performance, body morphometric measurements and testicular development in lambs fed with different rates of sunflower meal inclusion. The animals (24) were randomly distributed in treatments with 0, 10, 20 and 30% of sunflower meal in the dry matter of the diet, in six replicates, during 56 days of confinement. The addition of the coproduct at increasing dietary rates increased linearly the dry matter intake in the percentage of live weight and neutral detergent fiber. Despite this, there was a linear reduction in ether extract intake and chest width. On the other hand, there was no difference in daily, total and final weight gains. The body condition score; height of withers, croup and thorax; length of body and croup; width of fore croup, hind croup and chest; thoracic and neck diameters also did not change with the addition of the coproduct. The testicular measures 26.76; 6.11; 6.08; 5.22; 5.21; 4.80, and 4.81cm varied quadratically with the inclusion. Therefore, the inclusion of 30% of the coproduct changes nutrient intake and testicular biometry, but does not interfere in the body weight and development, being an economical alternative.